Synthesis and Anticancer Activity Evaluation of Novel Phenanthridine Derivatives - Wan, Minghui; Zhang, Lei; Chen, Yiming; Li, Qiang; Fan, Wenli; Xue, Qingxia; Yan, Fang; Song, Weiguo (Frontiers in Oncology, 2019)
In structural modification of sanguinarine, fourteen phenanthridine derivatives were designed and synthesized. The cytotoxic activities of synthesized compounds were evaluated against five human cancer cell lines (MCF-7, PC3, Hela, A549 and HepG2 cell lines) in vitro by MTT assay. Among all the compound tested, molecule 8a showed significant cytotoxic activity against MCF-7 cells with IC50 value of 0.28 µM. The enzymatic assay exhibited that compound 8a could inhibit the activity of DNA topoisomerase Ⅰ/Ⅱ. Further MCF-7 cell based mechanism studies revealed that compound 8a could lead cell cycle arrest in S phase, and induce cell apoptosis via downregulating the expression of Bcl-2 and upregulating the expression of Bax.